ANALISIS BUTIR SOAL TES MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL PADA SISWA KELAS VIII - Lestari, Agistia Suci; Fitrianna, Aflich Yusnita; Zanthy, Luvy Sylviana (IKIP Siliwangi, 2023)
This study aims to determine the quality of the test items for mathematics subjects on the material of a two-variable system of linear equations with a combined method. That the thing is that learning is limited by researchers will conduct research at SMP Negeri 2 Haurwangi with research subjects of class VIII students who are in class 05 which contains 17 students. In class 05, students have different characteristics, from high, medium, and low categories which can be obtained from the assessment of students' answers to the test questions given. The items made consist of 3 questions. With easy, medium, and difficult categories. Given this research is a research that uses quantitative descriptive which will be analyzed using Ms. Excel based on Validity, Reliability, Distinguishing Power and Difficulty Index. The results showed that; 1) the three items with very high validity and high reliability, 2) based on the discriminatory power of interpretation is less, 3) based on the difficulty index of question no. 1 and 2 are moderate, while question no. 3 is difficult.